The guidelines for the community knowledge management process for cultural tourism site development in Luang Prabang province, Lao People’s Democratic Republic - Phengxay, Vanglee; Andhivarothai, Porntip (Interdisciplinary Research Review, 2016)
The purpose of research was to propose guidelines for the community knowledge management process for cultural tourism site development in Luang Prabang province. This qualitative study involved documentary and field research by means of observation and in-depth interviews. The six major groups of key informants were community leaders, community officials, head of defense officials, souvenir manufacturers, members of women organizations, and government officials for total number of 39. The data were coupled with those from in-depth interviews with seven tourism sites development experts during the focus group discussion and from interviews with three knowledge management (KM) resource persons who helped review the draft guidelines. The findings are: The guidelines for the community KM process for cultural tourism site development, Luang Prabang province that begin with goals and objectives identification and establishment of practitioner communities consist of seven stages. There are 1) knowledge Identification; 2) knowledge creation and acquisition; 3) knowledge organization; 4) knowledge codification and refinement; 5) knowledge access; 6) knowledge sharing; and 7) learning. All stages are to be supported with information technology infrastructure.